La ficha cualitativa como herramienta etnográfica para evidenciar el favorecimiento del desarrollo del pensamiento tecnológico de niños y niñas - López Ortega, Diana Luz; Betancur Taborda, Martha; Palacio N., Olga; Torres M., Orlando (Revista Científica, 2012)
This article presents some results from the systematization of the inputs of the school experience in IV semester (teaching practice) through the years 2003 - I / 2006 - II, in the Bachelor of Children’s Pedagogy at the Science and Education Faculty in the Universidad Distrital “Francisco José de Caldas” Bogotá - Colombia. The purpose of this is for the fourth semester students to understand the meaning of the concepts of cultural device – to think technologically, and provide meaning to the pedagogical practices that they perform with children from 4 to 6 year old on average. The emphasis is placed on the qualitative data as ethnographic tool; the result is a methodological proposal, structured and made suitable for university students.